Analysis of rice Act1 5' region activity in transgenic rice plants. - Zhang, W (1991)
The 5' region of the rice actin 1 gene (Act1) has been developed as an efficient regulator of foreign gene expression in transgenic rice plants. To determine the pattern and level of rice Act1 5' region activity, transgenic rice plants containing the Act1 5' region fused to a bacterial beta-glucuronidase (Gus) coding sequence were generated. Two independent clonal lines of transgenic rice plants were analyzed in detail. Quantitative analysis showed that tissue from these transgenic rice plants have a level of GUS protein that represents as much as 3% of total soluble protein. We were able to demonstrate that Act1-Gus gene expression is constitutive throughout the sporophytic and gametophytic tissues of these transgenic rice plants. Plants from one transgenic line were analyzed for the segregation of GUS activity in pollen by in situ histochemical staining, and the inheritance and stability of Act1-Gus expression were assayed in subsequently derived progeny plants.